(untitled) (Journal of Informatics and Mathematical Sciences, 2019)
M-polynomial of different molecular structures helps to calculate many topological indices. A topological index of graph \(G\) is a numerical parameter related to \(G\) which characterizes its molecular topology and is usually graph invariant. In the field of quantitative structure-activity (QSAR), quantitative structure-activity structure-property (QSPR) research, theoretical properties of the chemical compounds and their molecular topological indices such as the Zagreb indices, Randic index, Symmetric division index, Harmonic index, Inverse sum index, Augmented Zagreb index, multiple Zagreb indices etc. are correlated. In this report, we compute closed forms of M-polynomial, first Zagreb polynomial and second Zagreb polynomial of octagonal network. From the M-polynomial we recover some degree-based topological indices for octagonal network.